Women in the IT sector: Is there an English language premium?. (1st January 2011) - Chandramohan, B.P.; Gajanan, Shailendra N.; Muthulakshmi, B.
Consistent with Human Capital Theory we show that observed earnings differentials are higher, based on the type of education. We track women employees in the Information Technology (IT) sector in Chennai, in the state of Tamil Nadu, India, and, estimate the source of earnings differential, and demonstrate the existence of an English language premium. That is, additional schooling generates higher returns, especially if the medium of instruction is in English. These findings have relevance for enrolment rates, poverty and women empowerment.